PET HEALTH EACOL: KNOWLEDGE ON INTRODUCTION OF HEALTHY COMPLEMENTARY FEEDING FOR PREGNANT WOMEN AND MOTHERS ATTENTED AT THE MUNICIPAL PROGRAM TO FIGHT MALNUTRITIONAL, CATAN - MACAÉ, RJ. (Fiep Bulletin - online, 2016)
Complementary feeding (CF) should be started from 6 months of the infant's life, which is, along with breastfeeding, reducing child mortality. This study aimed to describe the knowledge about the introduction of healthy CF of pregnant women and mothers of infants
Keywords: Infants; Pregnant Women; Complementary Feeding.